Commercial factor affecting service apartment overhang in Petaling district, Selangor: case study Rhythm Avenue USJ 19 / Muhammad Naufal Fakhrul Razy - Fakhrul Razy, Muhammad Naufal (2023)
According to the Valuation and Property Services Department's (JPPH) 2022 Property Market Report, Selangor had 2,926 overhang serviced apartment/SOHO units worth RM1 .74 billion in 2022. This was an increase of 624 units and RM310 million from 2021, when there were 2,302 overhang units worth RM1 .43 billion. The study investigate on the commercial factors affecting service apartment overhang in Petaling District, Selangor Case Study is at Rhythm Avenue USJ 19. The objectives include to identify the commercial factor and to rank the commercial factor affecting service apartment overhang in Petaling District, Selangor Case Study is at Rhythm Avenue USJ 19 The study focuses on service apartment located at Rhythm Avenue USJ 19, where access to data allows for comprehensive analysis. Data collection involves a literature review and questionnaire surveys. the questionnaire are being divided into two sections Section A is about respondents' personal information. This section is for gathering personal information such as gender. Section B poses questions regarding on commercial factor affecting service apartment overhang.